Communication Management of Republic of Indonesia Radio Broadcasters (Rri) Medan in Maintaining Its Existence in the Digitalization Era - Chairunnisa Nasution; Efi Brata Madya (LPPM Universitas Trunojoyo Madura, 2023)
Changes in consumer behavior in accessing information in the digitalization era have become a challenge for radio broadcaster RRI Medan to maintain its existence. Therefore, communication management needs to innovate and develop effective communication strategies to stay relevant and interesting to listeners. This research was conducted to determine the communication strategy of broadcaster RRI Medan in maintaining its existence in the digitalization era. This type of research is descriptive qualitative which aims to explain and describe. Researchers use content analysis in analyzing data. The data analysis used in this study is data reduction, data presentation, and conclusions. Radio conveys information and instructions to its listeners quickly, or it can be said that it is also delivered directly. Having a good communication strategy as well as interesting content really helps radio in maintaining its existence in society. In addition, Broadcasters are the spearhead for broadcast radio. The research results show that. RRI Medan also makes it easier for listeners to listen to broadcasts through the RRI play go application and other internet access. In this effort, RRI Medan can maintain its existence in the digitalization era